In vitro Study on Interaction of Ketotifen Fumerate with Paracetamol - Sayeed, Mohammed Aktar; Rana, Sohel (IIUC Studies, 2012)
Interaction of ketotifen fumerate and paracetamol was studied in aqueous media. The ability of interaction of ketotifen with paracetamol is dependent on pH of the solution and it has been found that ketotifen forms 1:1 complexes at different pH. The stability constants have been calculated from the Ardons spectrophotomeric measurements of the reaction systems. When ketotifen was interacted with paracetamol and the absorbance was determined at 300 nm the stability constants were found of - 7.32 and -7.84 at pH 1.6 and 7.4 respectively. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12258 IIUC Studies Vol.7 2011: 49-54